Synthesis of New Fused 4H-Thieno[3,2-b]pyrrole Derivatives via Decomposition of Methyl 4-Azido-5-arylthiophene-2-carboxylates - Samsonenko, Anna L.; Kostyuchenko, Anastasia S.; Zheleznova, Tatyana Yu.; Shuvalov, Vladislav Yu.; Vlasov, Igor S.; Fisyuk, Alexander S. (Synthesis, 2022)
This article is focused on the development of practical approaches to the synthesis of 4-azido-5-arylthiophene-2-carboxylates and 4-amino-5-arylthiophene-2-carboxylates using the Fiesselmann reaction. The photochemical and thermal (including microwave-assisted) decomposition of 4-azido-5-arylthiophene-2-carboxylates have been studied in order to synthesize fused 4H-thieno[3,2-b]pyrrole derivatives. The proposed approaches allow to obtain functionally substituted heteroacenes, which are of interest as building blocks for organic semiconductors.
Keywords: conjugation; cyclization; fused-ring system; heterocycles; amines; azides